Perovskite SrCo0.9Nb0.1O3−δ as an Anion-Intercalated Electrode Material for Supercapacitors with Ultrahigh Volumetric Energy Density - Zhu, L.; Liu, Y.; Su, C.; Zhou, W.; Liu, M.; Shao, Zongping (Wiley-VCH Verlag, 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, WeinheimWe have synthesized and characterized perovskite-type SrCo0.9Nb0.1O3-d(SCN) as a novel anion-intercalated electrode material for supercapacitors in an aqueous KOH electrolyte, demonstrating a very high volumetric capacitance of about 2034.6 F cm-3(and gravimetric capacitance of ca. 773.6 F g-1) at a current density of 0.5 A g-1while maintaining excellent cycling stability with a capacity retention of 95.7 % after 3000 cycles. When coupled with an activated carbon (AC) electrode, the SCN/AC asymmetric supercapacitor delivered a specific energy density as high as 37.6 Wh kg-1with robust long-term stability.